Традиції виховання дітей у білоруської шляхти в XIX–XX столітті - Ракова, Л. (Народна творчість та етнографія, 2009)
In the article within the limits of the systemic-functional approach the major features of family education traditions family of Byelorussians in XIXth –XXth centuries are considered; education and socialisation problems; mechanisms of transmission of cultural values of a family to the following generations; the role of labour activity as basic tradition of education of children at Byelorussians is analyzed.